Crystallization of Escherichia coli CdtB, the biologically active subunit of cytolethal distending toxin - Hontz, Jill S. (International Union of Crystallography, 2006)
Cytolethal distending toxin (CDT) is a secreted protein toxin produced by several bacterial pathogens. The biologically active CDT subunit CdtB is an active homolog of mammalian type I DNase. Internalization of CdtB and subsequent translocation into the nucleus of target cells results in DNA-strand breaks, leading to cell-cycle arrest and apoptosis. CdtB crystals were grown using microbatch methods with polyethylene glycol 8000 as the precipitant. The CdtB crystals contain one molecule of MW 30.5 kDa per asymmetric unit, belong to space group P2(1)2(1)2(1) and diffract to 1.72 Å.